Digital Library for the Decorative Arts and Material Culture - University of Wisconsin-Madison - Memorial Library (2001)
[Dt.:] Die digitale Bibliothek für Angewandte Kunst sammelt und produziert elektronische Ressourcen für Forschung und Lehre. Der Schwerpunkt liegt auf dem Kunsthandwerk des frühen Amerikas. Die digitale Bibliothek umfasst sowohl eine Volltextdatenbanken (u.a. auch historische, illustrierte Drucke) sowie Bilddatenbanken, E-Journals und sonstige Informationen über Organisationen, Museen oder Forschungsinstitutionen. - [Engl.:] The Digital Library for the Decorative Arts and Material Culture collects and creates electronic resources for study and research of the decorative arts, with a particular focus on Early America. Included are electronic texts and journals, image databases, and information on organizations, museums and research facilities. Made possible by the Chipstone Foundation, the site was created and is maintained at the University of Wisconsin-Madison Libraries.